COMPARATIVE ANALYSIS OF LINGUISTIC MEANS IN RUSSIAN AND UZBEK RIDDLES - Abdukahhorova, Nargiza (Zamonaviy filologiya muammolari, 2025)
The article investigates riddles as a manifestation of Russian and Uzbek oral folklore through the lens of linguocultural analysis. It examines the ways riddles encode historical, cultural, and aesthetic values, emphasizing their role in shaping national worldviews. Attention is given to imagery, symbolic representations, metaphors, and linguistic devices that express culturally specific perceptions. The comparative analysis reveals both convergences and divergences: Russian riddles often feature motifs linked to a cold climate and Orthodox tradition (forest, snow, church, bear), whereas Uzbek riddles are shaped by a warm environment and Islamic influences (sun, tandir oven, bread, land). The findings underline the intrinsic connection between language and culture and position riddles as cultural-linguistic codes with significant potential for fostering intercultural competence.